Hubungan Preeklamsia dengan Kejadian Berat Badan Lahir Rendah - Ni Made Delviani; Ni Nyoman Udiani; I Made Rio Dwijayanto (Universitas Widya Nusantara, 2025)
Low birth weight (LBW), defined as a neonate weighing less than 2,500 grams regardless of gestational age, remains a major cause of mortality, morbidity, and disability among neonates, infants, and children. Preliminary data at Nasanapura Mother and Child Hospital, Palu, showed an increase in LBW cases from 50 in 2020 to 109 in 2023, along with rising preeclampsia cases. This study aimed to analyze the association between preeclampsia and LBW incidence. This quantitative study employed a cross-sectional design. The study population consisted of 95 pregnant women diagnosed with preeclampsia between January and June 2024, with 35 respondents selected through purposive sampling. Data were obtained from medical records and analyzed using the Chi-Square test with a significance level of p<0.05. Most respondents experienced severe preeclampsia (60%), and 20 infants (57.1%) were born with LBW. Chi-Square analysis revealed a significant association between preeclampsia and LBW incidence (p=0.015), with an odds ratio of 0.125 (95% CI: 0.027–0.580), indicating that mothers with mild preeclampsia had a lower risk of delivering LBW infants compared to those with severe preeclampsia. Preeclampsia is significantly associated with increased LBW incidence at Nasanapura Hospital, Palu. Strengthening antenatal care services, early detection of preeclampsia, and routine maternal nutrition counseling are essential strategies to reduce LBW cases.